Effect of different packaging methods on the free amino acid profiles of the deep-water rose shrimp (Parapenaeus longirostris) during frozen storage - Rusanova, Polina; Bono, Gioacchino; Dara, Manuela; Falco, Francesca; Gancitano, Vita; Lo Brutto, Sabrina; Okpala, Charles Odilichukwu R.; Nirmal, Nilesh Prakash; Quattrocchi, Federico; Sardo, Giacomo; Hassoun, Abdo (Frontiers in Nutrition, 2022)
The composition of free amino acids (FAAs) in seafood products contributes towards characterizing their flavor, as well as freshness and quality during storage. Deep-water rose shrimps (Parapenaues longirostris, Lucas, 1846) (DWRS) are being increasingly harvested in the Mediterranean, and the captured animals are quickly frozen onboard fishing trawlers to preserve freshness and post-harvest quality. Here, we quantified the FAA profiles of DWRS packaged using five methods: (1) 100% N2; (2) vacuum; (3) 50% N2 + 50% CO2; (4) commercial anhydrous sodium sulfite; and (5) air (control). All samples were quickly frozen at -35 °C and stored for 12 months at -18 °C. Arginine (661 mg/100g), proline (538 mg/100g), and glycine (424 mg/100g) were the most abundant FAAs, followed by tyrosine (67 mg/100g), histidine (58 mg/100g), and aspartic acid (34 mg/100g). FAAs in all samples gradually (and signiicantly) increased in the first six to eight months of storage, and then significantly decreased. The sodium sulfite treatment (Method 4) kept the initial FAA contents lower than the other treatments, due to the strong antioxidant action of sulfite agents. Interestingly, similar results were obtained for vacuum packaging (Method 3). Thus, combining frozen storage with vacuum packaging (plus modified atmosphere techniques) represents an alternative approach to chemical additives in shrimp/prawn processing to meet the increasing demand for high-quality seafood products with long shelf-life.